2009
DOI: 10.1021/cm9022776
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Calcium Phosphate Heterogeneities in 2D-Hexagonal and 3D-Cubic SiO2−CaO−P2O5 Mesoporous Bioactive Glasses

Abstract: Mesoporous bioactive glasses (MBGs) with a compoisition of 85SiO 2 -10CaO-5P 2 O 5 (mol %) have been prepared through the evaporation-induced self-assembly (EISA) method, using P123 as a structure directing agent. For the first time, SiO 2 -CaO-P 2 O 5 MBGs with identical composition and textural properties, but exhibiting different bicontinuous 3D-cubic and 2D-hexagonal structures, have been prepared. These materials allow us to discriminate the role of the structure on the bioactivity, from other parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
105
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 38 publications
17
105
1
Order By: Relevance
“…Compared to conventional nonmesoporous bioactive glasses, the MBG possesses a more optimal surface area, pore volume, ability to induce in vitro apatite mineralization in simulated body fluids, and excellent cytocompatibility. [92][93][94][95] For better bone regeneration application, MBG can also be prepared as 3D porous scaffolds for bone tissue engineering and drug delivery applications. 96 Currently, there are three methods to prepare MBG scaffolds.…”
Section: Nanotechnology In Bone Regenerationmentioning
confidence: 99%
“…Compared to conventional nonmesoporous bioactive glasses, the MBG possesses a more optimal surface area, pore volume, ability to induce in vitro apatite mineralization in simulated body fluids, and excellent cytocompatibility. [92][93][94][95] For better bone regeneration application, MBG can also be prepared as 3D porous scaffolds for bone tissue engineering and drug delivery applications. 96 Currently, there are three methods to prepare MBG scaffolds.…”
Section: Nanotechnology In Bone Regenerationmentioning
confidence: 99%
“…in presence and absence of phosphorus, respectively, were prepared under the same experimental conditions. Moreover, the molar ratio between the network formers (SiO 2 + P 2 O 5 ) and surfactant was always kept constant [56]. Transmission electron microscopy (TEM) studies evidenced that in the presence of phosphorus, the mesoporous arrangement consisted of a threedimensional bicontinuous cubic structure while in the absence of phosphorus, the structure evolved to two-dimensional hexagonal (figure 3b).…”
Section: (A) Tailoring the Structural And Textural Properties Of Tempmentioning
confidence: 99%
“…The evaporation temperature used during the EISA process also affects the final mesostructure of TGs [56]. It has been observed that the structure of a TG evolves from three-dimensional bicontinuous cubic structure to two-dimensional hexagonal structure when decreasing the solvent evaporation temperature.…”
Section: (A) Tailoring the Structural And Textural Properties Of Tempmentioning
confidence: 99%
“…These are absent in FTIR spectrum of calcined MBG-TEP. A weak peak observed at 560 cm -1 shows the presence of calcium phosphate (Ca-P) clusters [24]. The small bands between 610 and 592 cm -1 are attributed to the m 2 and m 4 bending vibrations of O-P-O linkage in phosphate groups.…”
Section: Thermal Behaviour Of Mesoporous Bioactive Glassesmentioning
confidence: 99%